HUBUNGAN ANTARA KENAIKAN BERAT BADAN SELAMA KEHAMILAN DENGAN KEJADIAN KETUBAN PECAH DINI DI KABUPATEN WAJO - Alfitra Salam; Nadyah; Fhirastika Annisha Helvian (Perhimpunan Dokter Gizi Klinik Indonesia, 2021)
Background : Nutritional status could be used as an assessment of the risk of premature rupture of membranes. One way to determine the nutritional status of pregnant women is to calculate the gestational weight gain of women based on body mass index before pregnancy. Objective : The purpose of this study was to determine the relationship between gestational weight gain and the occurrences of premature rupture of membranes. Methodology : An observational analytic study with a cross sectional approach was adopted in this study. The data of this study were collected from the patients’ medical records at RSUD Lamaddukelleng of Wajo Regency in which the inclusion and exclusion sampling criteria were used. A total of 90 samples of patients’ medical record was obtained related to premature rupture of membranes. The collected data were processed and analyzed using the Chi-Square test with the p value of <0.05. Result : The results of the study indicated that there was a significant relationship between weight gain during pregnancy and the occurrence of premature rupture of membranes with the p value of 0.016. Conclusion : This study concluded that while there is a significant relationship between weight gain during pregnancy and premature rupture of membranes